Mitochondria: It is all about energy - Casanova, Amaloha; Wevers, Anne; Navarro-Ledesma, Santiago; Pruimboom, Leo (Frontiers in Physiology, 2023)
Mitochondria play a key role in both health and disease. Their function is not limited to energy production, but serve multiple mechanisms varying from iron and calcium homeostasis to the production of hormones and neurotransmitters such as melatonin. They enable and influence communication at all physical levels, through interaction with other organelles, the nucleus, but also with the outside environment. Literature suggests crosstalk mechanisms between mitochondria and circadian clocks, the gut microbiota, and the immune system. They might even be the hub supporting and integrating activity across all these domains. As such, they might be the (missing) link in both health and disease. Mitochondrial dysfunction is related to metabolic syndrome, neuronal diseases, cancer, cardiovascular, infectious diseases, and inflammatory disorders. In this regard, diseases such as cancer, Alzheimer's, Parkinson's, Amyotrophic Lateral Sclerosis, chronic fatigue syndrome and chronic pain are discussed. This review focuses on the of understanding mitochondrial mechanisms of action that allow for the maintenance of mitochondrial health, as well as the pathways towards dysregulated mechanisms. While mitochondria have allowed us to adapt to changes over the course of evolution, in turn evolution has shaped the mitochondria. Each of the evolution-based interventions influences mitochondria in their very own way. The use of physiological stress triggers enhances tolerance to the stressor, achieving adaptability and resistance. This review describes possible strategies that could recover mitochondrial functioning in multiple diseases, providing a comprehensive, root-cause-focused, integrative approach to recover health and treat people suffering from chronic disease.